Optoelectronic oscillators for communication systems - Romeira, Bruno (2010)
We introduce and report recent developments on a novel five port optoelectronic voltage controlled oscillator consisting of a resonant tunneling diode (RTD) optical-waveguide integrated with a laser diode. The RTD-based optoelectronic oscillator (OEO) has both optical and electrical input and output ports, with the fifth port allowing voltage control. The RTD-OEO locks to reference radio-frequency (RF) sources by either optical or electrical injection locking techniques allowing remote synchronization, eliminating the need of impedance matching between traditional RF oscillators. RTD-OEO functions include generation, amplification and distribution of RF carriers, clock recovery, carrier recovery, modulation and demodulation and frequency synthesis. Self-injection locking operation modes, where small portions of the output electrical/ optical signals are fed back into the electrical/optical input ports, are also proposed. The self-phase locked loop configuration can give rise to low-noise high-stable oscillations, not limited by the RF source performance and with no need of external optoelectronic conversion.